DIMENSI CORPORATE ENTREPRENEURSHIP DAN PENGARUHNYA TERHADAP KINERJA PERUSAHAAN - Mulyanto, Kukuh (STIE Totalwin Semarang, 2013)
This research examine the effects of corporate entrepeneurship on firm performance. Summary said that corporate entrepeneurship is positively effected to firm performance